Authoritarian Surveillance: An Introduction - Volinz, Lior (Surveillance & Society, 2025)
Authoritarian surveillance is no longer an exceptional or rare practice. In many parts of the world, we are witnessing an increase of pervasive government monitoring, of curtailing privacy protections, of stringent control of information flows, and of intimidation towards self-censorship. These hallmarks of authoritarian surveillance are not confined to authoritarian or undemocratic regimes. In a political landscape that favours strongarm authoritarian leaders, the boundaries between authoritarian and democratic regimes, the liberal and the illiberal ones, are blurrier than ever. The increasing availability of advanced technologies for analyzing (big) data, particularly when integrated with artificial intelligence (AI), has heightened the temptation for governments to adopt authoritarian surveillance tools and practices—and has amplified the potential dangers involved.This Dialogue section introduces the multiple dimensions of contemporary authoritarian surveillance, going beyond a dichotomy between “democratic” and “authoritarian” regimes to identify and map authoritarian surveillance in diverse geographical and political contexts. We focus on surveillance beyond the exceptional and beyond the rule of law to examine an increasingly mundane but dangerous practice undermining the limited democratic spaces that remain in our world. The seven articles in this special Dialogue section explore different angles of authoritarian surveillance— the technologies that facilitate it, the laws that govern it, and the legacies that precede it or linger thereafter—and the social and political consequences that emerge as a result. Together, this collection revisits existing literature on authoritarian surveillance, calls for a renewed scholarly focus on its consequences, and proposes new directions for future research.